Sistem pendukung keputusan dalam menentukan balita stunting menggunakan metode Simple Additive Weighting (SAW) berbasis website - Sari, Mega Purnama; Wijaya, Dhina Puspasari; Pramuntadi, Andri; Danianti, Dita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The health center that has the highest prevalence of stunting in Sleman Regency is the Minggir health center at 13.15%. The results of interviews with nutrition officers for toddlers at the Minggir Health Center showed that there were still toddlers with poor nutritional status. In addition, the nutrition service system for toddlers has not functioned properly.  Because such suboptimal performance will, it is easier to create a system that can handle or minimize such problems. Thus, building a decision support system can be a solution to the problem that occurs. The SAW method is one of the methods used and the system is designed using the PHP programming language, MySQL database and  laravel framework. The research resulted in the creation of a website that can determine the nutritional status of stunted toddlers at the Minggir Health Center Posyandu. This system is designed according to the needs based on the criteria that have been set by the nutrition officer. In the application test, the preference values and nutritional status results obtained from calculations using the system were in accordance with the results of manual calculations with Excel and the nutritional status determination system was as expected.